Answer:
A
Step-by-step explanation:
Replace the point (0,0) in each inequality
A. y - 4 < 3x - 1
B. y - 1 < 3x - 4
C. y + 4 < 3x - 1
D. y + 4 < 3x + 1
A. 0 - 4 < 3(0) - 1
- 4 < - 1
True
B. 0 - 1 < 3(0) - 4
- 1 < - 4
False
C. y + 4 < 3x - 1
0 + 4 < 3(0) - 1
4 < - 1
False
D. y + 4 < 3x + 1
0 + 4 < 3(0) + 1
4 < 1
False
No. 5 or 6 would be, though.
Step-by-step explanation:
3x² - 8x + 4 =
3x² - 6x -2x + 4 =
3x(x-2) -2(x-2) =
(3x -2)(x-2)
Answer:
Step-by-step explanation:
A/4=72/12
A=4(72)/12
A=24 u^2